2021
DOI: 10.1111/bjh.17813
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anti‐SARS‐CoV‐2 vaccination for patients with immune thrombocytopenia

Abstract: Severe coronavirus disease 2019 , due to the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), may be associated with mild thrombocytopenia, 1,2 and some COVID-19-induced immune thrombocytopenia (ITP) cases have been reported. 3,4 Some reports suggest that patients with pre-existing ITP may experience a relapse 5 in the case of SARS-CoV-2 infection that could be prevented by vaccination. However, a growing number of de novo ITP occurring after anti-SARS-CoV-2 vaccination are being reported with mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
4
17
0
2
Order By: Relevance
“…In contrast, a study of 92 ITP patients who mostly received the BNT162b2 vaccine, did not observe decreased platelet count after first and second vaccination. 12 In our mixed-effects model, we did observe a significant decrease of platelet counts of 6.3% in ITP patients after COVID-19 vaccination. As there is a high degree of interand intra-individual variability in platelet counts over time, we systemically measured patients over a longer observation period and corrected for inter-and intra-individual variability.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In contrast, a study of 92 ITP patients who mostly received the BNT162b2 vaccine, did not observe decreased platelet count after first and second vaccination. 12 In our mixed-effects model, we did observe a significant decrease of platelet counts of 6.3% in ITP patients after COVID-19 vaccination. As there is a high degree of interand intra-individual variability in platelet counts over time, we systemically measured patients over a longer observation period and corrected for inter-and intra-individual variability.…”
Section: Discussionmentioning
confidence: 59%
“…Other observational studies found comparable incidences between 12 to 25%. [11][12][13] . The amount of patients needing rescue medication was 6.9% in our study compared to 8.7% in the study of Crickx, et al 12 In other autoimmune diseases, exacerbation of symptoms after COVID-19 vaccination has anecdotally been described, with rapid remission after glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for ITP relapse with vaccination include ongoing treatment, old age [ 164 ], and post-splenectomy status or a long history of prior treatment [ 165 ]. In terms of platelets, low platelet counts are reportedly associated with a higher risk of relapse [ 164 ], and platelet counts often decrease rapidly in patients with normal platelet count [ 166 ]. Regardless of the platelet count, attention should be paid to transition of the platelet count in ITP patients.…”
Section: Sars-cov-2 Vaccination-associated Coagulopathymentioning
confidence: 99%